Problem Based Learning Video on Force Material for Fourth Grade of Elementary School - Maharani, Ni Putu Putri Prananda; Suniasih, Ni Wayan; Sujana, I Wayan (Universitas Pendidikan Ganesha, 2024)
Facts in the field show that teachers do not use enough problem-based learning media when teaching. This has an impact on students' low problem-solving abilities. This study aims to analyze the effectiveness of problem-based learning video media for the subject of science, the material of the forces around us, grade IV elementary school. The type of research conducted is development research using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this study were 33 grade IV students. The method and instrument for data collection used questionnaires and tests. Data were analyzed using quantitative descriptive analysis techniques and inferential statistics. The results of trials by experts and practitioners showed that the learning media were included in the good category and were declared very suitable for use in the learning process. The results of the media effectiveness test on student learning outcomes stated that H0 was rejected and H1 was accepted. Thus, it can be concluded that media innovation in the form of problem-based learning videos for the subject of science, the material of the forces around us, grade IV elementary school has proven to be effective in its application. This study has implications for increasing teacher participation in using problem-based learning video media to develop students' ability to solve problems.